Pengaruh CSR, Profitabilitas, dan Leverage Terhadap Manajemen Laba dengan Kualitas Audit sebagai Variabel Moderasi - Rusliyawati Rusliyawati (JAAKFE UNTAN (Jurnal Audit dan Akuntansi Fakultas Ekonomi Universitas Tanjungpura), 2023)
The purpose of this study is to examine the relationship of corporate social responsibility (CSR) on earnings management and the impact of and audit firm size on the association between corporate social responsibility (CSR) and earnings management, the association between Profitability and Earning Management and the association between Leverage and Eaning Management. The dependent variable that used in this study is earnings management. Corporate social responsibility (CSR), Profitability, and Leverage used as independent variable. Furthermore, this study used audit firm size as a moderating variable. The sample in this study consists of 117 mining companies that listed on Indonesia Stock Exchange in the period 2016-2020. The data that used in this study was secondary data and selected by using purposive sampling method. The technique of analysis used for examining the hypothesis was multiple regression analysis Based on the empirical results of this study show that corporate social responsibility (CSR) has positive significant influence on earnings managements but not significant in profitability and leverage with earning management. This study did not find the association of audit firm size between profitability and earnings management, but this study found the association of audit firm size between corporate social responsibility (CSR) and earnings management and also found the association of audit firm size between leverage and earning management.